The Urban Sketching Handbook Understanding Light - Woodward, Katie (Quarry Books, 2021)
The Urban Sketching Handbook: Understanding Light helps urban sketchers develop the skills they need to capture and express different kinds of light, both natural and artificial, in both day and night scenes.